The large-scale problem - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
A commercial farmer from Cameroon discusses the difficulty of large-scale organic production, and a plant health specialist comments on crop rotation and organic market development.